The presence of heparan sulfate in the mammalian oocyte provides a clue to human sperm nuclear decondensation in vivo - Romanato, Marina (2008)
BACKGROUND: Previous results from our laboratory have led us to propose heparan sulfate (HS) as a putative protamine acceptor during human sperm decondensation in vivo. The aim of this paper was to investigate the presence of glycosaminoglycans in the mammalian oocyte in an effort to better support this contention. METHODS: Two experimental approaches are used: oocyte labeling to identify the presence of HS and analysis of sperm decondensing ability of fresh oocytes in the presence or absence of specific glycosidases. RESULTS: Staining of mouse zona-intact oocytes with the fluorescent cationic dye, Rubipy, at pH 1.5 allowed for the detection of sulfate residues in the ooplasm by confocal microscopy. HS was detected in the ooplasm by immunocytochemistry. A sperm decondensation microassay using heparin and glutathione was successfully developed. The same level of sperm decondensation could be attained when heparin was replaced by mouse zona-free oocytes. Addition of heparinase to the oocyte/glutathione mixture significantly reduced sperm decondensation (P = 0.0159), while there was no effect following addition of either chondroitinase ABC or hyaluronidase. CONCLUSIONS: The results presented in this paper demonstrate for the first time that HS is present in the mammalian oocyte and show that HS is necessary for fresh oocytes to express their sperm decondensing ability in vitro. © The Author 2008. Published by Oxford University Press on behalf of the European Society of Human Reproduction and Embryology. All rights reserved.